FSO/CV-QKD/QBaudSK system based on 2PolSK-BPSK scheme considering dynamical atmospheric conditions - López-Leyva, Josué Aarón; Ponce Camacho, Miguel Ángel; Estrada-Lechuga, Jessica; Mejía González, Efraín Atenógenes (My University, 2019)
In this paper, an FSO/CV-QKD/QBaudSK system using WCS and coherent detection for dynamical atmosphericconditions emulated by atmospheric turbulence box is presented. In particular, two systems (Alice and Bob) were designed and implemented in order to perform a conventional QKD algorithm using a unidirectional free space channel (private channel) and a bidirectional classical channel (public channel). The preliminary results obtained were related to the performance of the Degree of Polarization of the QWP and PolM considering and non-considering dynamical atmospheric conditions. The results showed the proposed method to be feasible for different weather conditions based on the BER using a 2PolSK-BPSK modulation.
SPIE Proceedings
Keywords: Turbulence; Free-space-optics; State of polarization; Quantum key distribution; Degree of polarization; Phase-shift keying